Proceedings of the International Conference on Islamic Education (ICIE 2018) 2018
DOI: 10.2991/icie-18.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Development of Student Worksheet Based on a Scientific Approach for Rotational Dynamics Concept

Abstract: Experience is divided into learning. Student worksheet is used as a medium to train students' critical skills. The research design used is ADDIE approach. The ADDIE stage it uses Analysis, Design, Development, Implementation, and Evaluation. Validation testing of some experts is a way to look at the feasibility of student worksheet and conduct tests (pretestposttest) to determine whether or not improvement of critical thinking skills of learners. The sample used in the research is student first semester of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…SW which contains steps for conducting experiments in accordance with the syntax of the Scientific approach, namely 5 M which makes students more enthusiastic in the learning process. Based on the results of research conducted by Suhendi, (2018), it was found that students' critical thinking skills can be developed through learning using worksheets based on a scientific approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SW which contains steps for conducting experiments in accordance with the syntax of the Scientific approach, namely 5 M which makes students more enthusiastic in the learning process. Based on the results of research conducted by Suhendi, (2018), it was found that students' critical thinking skills can be developed through learning using worksheets based on a scientific approach.…”
Section: Resultsmentioning
confidence: 99%
“…Problem solving skills can also be trained through providing direct experience to students by giving work orders in the form of sheets contained in the SW, this is in accordance with the results of research conducted by Elwi et al (2017) and Meutia et al (2021) who found that learning using SW can make students motivated and active in learning physics which leads students to find concepts in understanding the material. Previous research on the Scientific approach has been carried out by several researchers, such as the research conducted by Suhendi, (2018) which found that the improvement of students' critical thinking skills after applying the scientific approach in the classroom showed positive and promising results.…”
Section: Introductionmentioning
confidence: 99%
“…The learning module is one of the printed and digital learning media. Learning modules can be used as a learning resource to accommodate students' higher-order thinking skills (Suhendi, Mulhayatiah, Yuningsih, et al, 2018). Learning modules are complete units to support the learning activities that are structured to assist students in achieving a number of objectives or competencies (Christoyadi et al, 2016;McClean, Attardi, Faden, & Goldsmidt, 2016;Mirkouei, Bhinge, McCoy, Haapala, & Dornfeld, 2016;Ruipérez-Valiente, Muñoz-Merino, Leony, & Kloss, 2015).…”
Section: Introductionmentioning
confidence: 99%